Effects of sediment transport on flood hazards : Lessons learned and remaining challenges - Vázquez-Tarrío, D. (Elsevier, 2025)
Sediment transport (bedload and suspension) plays a relevant role in the morphological response of river channels to large floods. Sediment load controls erosion and aggradation patterns during high flows, drives the migration of macroforms and contributes to the definition of thresholds for bank erosion and channel instability. Given this influence on channel morphology, it is clear that sediment transport influences both the channel geometry and water stage reached during floods and should therefore be considered in flood hazard analysis. So far, however, legislation on flood hazard and flood management plans still continues to typically disregard sediment transport. This is due mainly to the paucity of available data on sediment transport and the lack of standardized approaches for its integration into flood hazard analysis. The present work, which aims to provide some guidance on how to advance in this issue, has undertaken a bibliometric study and thorough review of the published scientific literature that had previously addressed the implications of sediment transport on flood hazards assessment. This review showed that: i) most studies on the influence of sediment transport on flood risk have focused on mountain streams, as they are highly sensitive systems to changes in sediment supply; ii) research has also focused on explaining historical changes in channel-conveyance capacity and flood frequency based on long-term trends in sediment supply; and iii) recent developments in hydrodynamic and morphodynamic numerical models provide opportunities to explicitly incorporate sediment transport in flood hazard analysis. However, despite the recent advances, we have identified important challenges and discussed needs to better consider sediment transport in flood hazards at different spatial and temporal scales.